Alkaline phosphatase activity and immunoglobin concentration in in-vitro uterine flushings of buffaloes (Buba/us bubalis) - PROMOD, K; MAHMOOD, S; TELANG, A G; SINGH, R; BISHT, G S (The Indian Journal of Animal Reproduction, 2023)
Alkaline phosphatase activity and immunoglobulin concentration during follicular phase, luteal phase (early, mid andlate), inactive ovarian stage and infected uterine flushing in-vitro was studied in buffalo uteri (n=SS) collected from local abattoir.The alkaline phosphatase activity varied significantly (P
Keywords: Buffaloes; uterine flushing; immunoglobulins; alkaline phosphatase